A colorimetric sensing method for direct determination of the adsorption capacity of colored cations in adsorbents - Siyang Xing; Congle Li; Jialin Wang; Mengmeng Sun; Yingying Zhao; Yixing Gou; Panpan Zhang; Jingtao Bi (npj Clean Water)
Abstract Adsorption capacity is a critical indicator of adsorbent performance, its assessment often requires precise but complicated measurements of adsorbate concentration in the liquid phase. This study presents a colorimetric sensing method based on a fabricated model for directly assessing the adsorption capacity of colored cations through the absorbance of the adsorbent. The exceptional analytical capability of the proposed method was demonstrated by the rapid determination of colored cation adsorption capacity in single-cation (Co(II), Ni(II), Cu(II), and U(VI)) systems, mixed-cation systems, and real wastewater samples. Additionally, a series of colorimetric cards have been developed to enable rapid and effective real-time monitoring of adsorption capacity in industrial production, resource extraction, wastewater treatment, and other applications. This research is expected to significantly enhance the methods available for adsorption capacity measurement.